NATIONALISM AND POLITICAL THOUGHTS OF SHEIKH M. ARSYAD THALIB LUBIS (1908-1972) - Harahap, Mardian Idris (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2021)
Abstract: This article describes the Nationalism and political thought of Sheikh M. Arsyad Talib Lubis (Tuan Arsyad). Tuan Arsyad's political ideology is religious nationalist in style, and his political thought is characterized as integrism in typology. His political views were inspired by his knowledge and understanding of Islamic sciences (especially fiqh or Islamic law). Sheikh M. Arsyad Thalib Lubis' political ideas and fatwas had a significant impact in instilling a sense of nationalism among Muslim youngsters, particularly in North Sumatra, in fighting colonialism and eradicating Communism. However, his political views on communism were challenged and criticized by Soekarno (the first President of Indonesia ) who labelled them as communist phobia and an unethical conduct. Donald E Weatherbee characterized Sheikh M. Arsyad Thalib Lubis' ideas against President Soekarno as a group that engaged in insubordination and posed a threat of punishment.Keywords: ulama, M. Arsyad Thalib Lubis, Islamic political view(s), religious nationalist, integrism